2015
DOI: 10.1007/s13592-015-0389-3
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of miRNAs related to caste differentiation in the honey bee, Apis mellifera

Abstract: -Honey bees are very important eusocial insects and are involved in the pollination of many plants. Queen bees and worker bees can develop from the same fertilized eggs and are thus genetically identical despite their substantial behavioral and physiological differences. The mechanism governing developmental differences between worker and queen bees has always attracted much interest. While there are several reports on messenger RNA (mRNA) expression related to caste differentiation or microRNA (miRNA) express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 52 publications
1
21
0
5
Order By: Relevance
“…Corresponding author: F. Böhme, franziska.boehme@uni-hohenheim.de Manuscript editor: Monique Gauthier et , Asencot and Lensky 1984, Kamakura 2011, Shao et al 2014, Buttstedt et al 2016, Guo et al 2016. RJ is responsible for the colonies well-being and physical fitness as it is fed to both larvae during the first few days after hatch and during the whole life of the queen (Haydak 1970).…”
Section: Introductionmentioning
confidence: 99%
“…Corresponding author: F. Böhme, franziska.boehme@uni-hohenheim.de Manuscript editor: Monique Gauthier et , Asencot and Lensky 1984, Kamakura 2011, Shao et al 2014, Buttstedt et al 2016, Guo et al 2016. RJ is responsible for the colonies well-being and physical fitness as it is fed to both larvae during the first few days after hatch and during the whole life of the queen (Haydak 1970).…”
Section: Introductionmentioning
confidence: 99%
“…With the development of next-generation sequencing, increasing numbers of miRNAs were identified and characterized from non-model organisms. It was demonstrated that miRNAs play an important role in regulating the biological and pathological processes by binding to the mRNA sequences of target genes at the stage of transcription and post-transcription (Plasterk 2006;King et al 2011;Guo et al 2016;Macedo et al 2016). As the content of miRNAs is approximately 0.01-0.1% of the total RNA present in the tissue, it is critical for the accurate measurement of those low abundance miRNAs to master its functions.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it can switch the reproductive mode and development (Quah et al 2015). Recent research showed that the expression levels of miRNAs were associated with honeybee diverse biological functions, such as ovarian activity, caste differentiation, and foraging behavior Guo et al 2016;Macedo et al 2016). In bumblebees, miRNAs have been described as an important gene in the regulation of bumblebee queen egg-laying (Sun et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Female honeybees are divided further into two castes, queens and workers, which differ in morphology, physiology and social function. Larvae receive a series of specific food stimuli including the administration of different miRNA sets, leading to morphological and structural changes [100]. In particular, during the 4th to 6th day of larval development honeybees are fed with two types of mush: (a) royal jelly, a glandular secretion of nurse bees, causing the stimulation of differentiation to queen bee and drones, the latter differing from queen because of their aployd genome; (b) beebread, composed of a fermented mixture of plant nectar and pollen, leading to the worker phenotype [101,102].…”
Section: The Influence Of Mirnas Contained In Food On Development: Thmentioning
confidence: 99%